01 Decoding Gender Ideologies Constructed in the Discourses of Khawateen Digest (Journal of Gender and Social Issues, 2017)
This research is an attempt to provide useful insights regarding certain „stereotypical? gender ideologies by defining femininities in terms of particular adjectives. These linguistic items are loaded with negative connotations and project the „marginalized? and „subordinate? roles of women in the patriarchal society of Pakistan. The present research explores the ambivalence inherent in these ideologies and highlights how these constructions of femininity and socialization of women in the discourses of a popular Pakistani magazine Khawateen Digest may lead the readers (mostly females) to internalize or even imitate these images. Data have been collected from the population of 300 (consisting of four age groups) through questionnaire. The findings make it clear that the construction of the ideologies of woman as “other” in these Digests confirm the specific roles of women tto  identify themselves in these particular terms only; never  thinking to pursue other independent and empowered roles and identities for themselves.
Keywords: Gender; Ideology; Patriarchy; Femininity; Identities